Thermo-optical vacuum testing of Galileo In-Orbit Validation laser retroreflectors. Issue 11 (1st June 2016) - Dell'Agnello, S.; Boni, A.; Cantone, C.; Ciocci, E.; Contessa, S.; Delle Monache, G.; Lops, C.; Martini, M.; Patrizi, G.; Porcelli, L.; Salvatori, L.; Tibuzzi, M.; et al.
Abstract: The Galileo constellation is a space research and development program of the European Union to help navigate users all over the world. The Galileo IOV (In-Orbit Validation) are the first test satellites of the Galileo constellation and carry satellite laser retroreflectors as part of their payload systems for precision orbit determination and performance assessment. INFN-LNF SCF_Lab (Satellite/lunar/GNSS laser ranging/altimetry and Cube/microsat Characterization Facilities Laboratory) has been performing tests on a sample of the laser array segment under theThermo-optical vacuum testing of Galileo IOV laser retro-reflectors of Galileo IOV LRA project, as defined in ESA-INFN Contract No. 4000108617/13/NL/PA. We will present the results of FFDP (Far Field Diffraction Pattern) and thermal relaxation times measurements in relevant space conditions of Galileo IOV CCRs (Cube Corner Retroreflectors) provided by ESA-ESTEC. A reference for the performance of laser ranging on Galileo satellites is the FFDP of a retroreflector in its design specifications and a Galileo retroreflector, in air and isothermal conditions, should have a minimum return intensity within the range [ 0.55 × 10 6 m 2 – 2.14 × 10 6 m 2 ] (ESA-INFN, 2013). Measurements, performed in SCF_Lab facility, demonstrated that the 7 Galileo IOV laser retroreflectors under test were compliant with design performance expectations (Porcelli et al., 2015). The kind of tests carried out for this activity are the first performed on spare Galileo IOV hardware, made available after the launch of the four Galileo IOV satellites (2011 and 2012), which were the operational core of the constellation. The characterisation of the retroreflectors against their design requirements is important because LRAs (Laser Retroreflector Arrays) will be flown on all Galileo satellites.